Efficacy and determinants of vacuum bell treatment in preschool children with pectus excavatum - Luo, Dengke; Cheng, Kaisheng; Yuan, Miao; Xu, Chang; He, Taozhen (Frontiers in Pediatrics, 2022)
Background: The outcome of vacuum bell (VB) treatment for preschool patients with pectus excavatum (PE) is poorly understood. We aim to investigate the treatment effect of VB with a three-dimensional scanner and assess the clinical and demographic factors that might influence treatment outcomes. Methods: We conducted a chart review study to review the records of preschool patients with PE who received VB treatment in a tertiary hospital from January 1, 2021, through January 1, 2022. Demographic data and chest wall deformity assessments were recorded at follow-up, including the anterior chest wall depths and depth ratio (DR). The demographic and clinical factors influencing treatment outcomes were tested using a logistic regression model. Receiver operating characteristic (ROC) curves were used to illustrate the results. Results: 139 patients who accepted vacuum bell treatment were included in the final study analysis, with a mean age of 4.6 years and BMI of 14.9. Forty-three patients (30.9%) with a depth of less than 3 mm met the termination criteria and showed cosmetic results. The changes in depths (P < 0.001) and DR (P < 0.001) were statistically significant in 55 patients with three follow-ups. Multifactor logistic regression analysis showed that initial depth (OR 0.69, 95% CI 0.58 - 0.84, P < 0.001) and treatment period (OR 1.58, 95% CI 1.23 - 2.04, P < 0.001) were independent predictors of achieving complete correction. ROC curve analysis determined an optimal cutoff level of 8.4 mm in the initial depths and 8.5 months in the treatment periods. Conclusion: VB is an effective modality in preschool patients. Moreover, a better outcome may be achieved in patients with initial depths ≤ 8.4 mm or treatment periods ≥ 8.5 months. However, further prospective studies are needed to confirm these results.